2021
DOI: 10.14744/nci.2021.91328
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood groups on the risk of COVID 19 infection, morbidity and mortality

Abstract: T he novel coronavirus-19 disease due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus was first reported in Wuhan, China, in December 2019 [1]. Since then, it has spread throughout the World with significant morbidity and mortality. In March 2020, the World Health Organization (WHO) reported COVID-19 as a pandemic and, over time, reported 110749023 confirmed cases of infection and 2455131 deaths until February 22, 2021 [2]. Due to the high morbidity and mortality associated withABS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Several existing risk factors can increase the susceptibility to COVID-19 infection and worsen clinical impacts in critically ill patients. 11 , 13 Evidence that supports the association between the Rh blood group and COVID‐19 infection in critically ill patients is not well established. The magnitude of the COVID-19 predisposition between two phenotype groups was reported inconsistently in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several existing risk factors can increase the susceptibility to COVID-19 infection and worsen clinical impacts in critically ill patients. 11 , 13 Evidence that supports the association between the Rh blood group and COVID‐19 infection in critically ill patients is not well established. The magnitude of the COVID-19 predisposition between two phenotype groups was reported inconsistently in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported studies did not show any association between Rh-blood groups and hospital length of stay. 11 , 13 , 24 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Turkish population, studies examining this risk were conducted [15][16][17]. The joint results found in these studies; people with group A are more likely to be infected, but the blood group does not have a significant effect on the course of the diseaseexcept for the study of Sertbas et al, which showed that the risk of intubation increased in the AB group [16]. It is seen in this study that the risk in group A, which we also confirmed before, is not valid for the period in which the current waves with delta and omicron variants.…”
Section: Discussionmentioning
confidence: 99%